2022
DOI: 10.21203/rs.3.rs-1958526/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A selective laser-based sensor for fugitive methane emissions

Abstract: A mid-infrared laser-based sensor is reported for the quantification of fugitive methane emissions. The sensor is based on a distributed feedback inter-band cascade laser (DFB – ICL) operating near 3.3 µm. Wavelength tuning with cepstral analysis is employed to isolate methane absorbance from (1) fluctuations in the baseline laser intensity, and (2) interfering species. Cepstral analysis creates a modified form of the time-domain molecular free-induction-decay (m-FID) signal to temporally separate optical and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In order to achieve high accuracy, the measurements had to be performed at flight altitudes between 4 and 15 m above the ground. These results were in agreement with investigations performed earlier [142], in which a similar set-up was used to detect subsurface and surface methane leaks. The authors also reported that the system was not able to discriminate between low and high concentration methane plumes.…”
Section: Urban Air Quality Monitoringsupporting
confidence: 92%
“…In order to achieve high accuracy, the measurements had to be performed at flight altitudes between 4 and 15 m above the ground. These results were in agreement with investigations performed earlier [142], in which a similar set-up was used to detect subsurface and surface methane leaks. The authors also reported that the system was not able to discriminate between low and high concentration methane plumes.…”
Section: Urban Air Quality Monitoringsupporting
confidence: 92%
“…Laser-based sensors can thus overcome many of the limitations associated with other speciation techniques [7]. Given these advantages, laser-based sensors have garnered attention from researchers and have been proven to be a useful tool for quantitative analysis of gaseous species in numerous elds, such as chemical analysis [8], monitoring of agricultural emissions [9], control of industrial processes [10], breath analysis [11], pollution monitoring [12][13][14], and combustion diagnostics [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the mid-infrared (MIR) region contains the fundamental vibrational bands of most of the atmospheric species and VOCs (e.g., CO 2 , H 2 O, hydrocarbons, etc.) [19,20]; the absorption coe cients of these species are orders of magnitude stronger in this region than in the near-infrared region [21]. A speci cally interesting region in the MIR is the molecular ngerprint region (6.7-20 m) which includes strong bending vibrational modes of many air pollutants and the C-halogen stretching modes of most halocarbons [22].…”
Section: Introductionmentioning
confidence: 99%
“…show overlapping absorption features over most of the IR range, which necessitates the use of advanced post-processing techniques in order to selectively measure BTEX species [23][24][25]. However, standard scanned-wavelength absorption spectroscopy would be su cient for selective detection due to the isolated, distinct features of BTEX in the molecular ngerprint region.…”
Section: Introductionmentioning
confidence: 99%